2022
DOI: 10.1136/emermed-2022-212443
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between blood pressure and pulse oximetry accuracy: an observational study in patients with suspected or confirmed COVID-19 infection

Abstract: BackgroundPulse oximeters are a standard non-invasive tool to measure blood oxygen levels, and are used in multiple healthcare settings. It is important to understand the factors affecting their accuracy to be able to use them optimally and safely. This analysis aimed to explore the association of the measurement error of pulse oximeters with systolic BP, diastolic BP and heart rate (HR) within ranges of values commonly observed in clinical practice.MethodsThe study design was a retrospective observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Similarly, Crooks et al demonstrated an inverse relationship between blood pressure and pulse oximetry accuracy. It has been reported that at low blood pressure, signal integrity received from translucent tissue is compromised due to poor peripheral perfusion, resulting in false overestimation of pulse oximetry readings [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Crooks et al demonstrated an inverse relationship between blood pressure and pulse oximetry accuracy. It has been reported that at low blood pressure, signal integrity received from translucent tissue is compromised due to poor peripheral perfusion, resulting in false overestimation of pulse oximetry readings [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Crooks et al demonstrated an inverse relationship between blood pressure and pulse oximetry accuracy. It has been reported that at low blood pressure, the signal integrity received from translucent tissue is compromised due to poor peripheral perfusion, resulting in the false overestimation of pulse oximetry readings [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study, which reported an inverse association between blood pressure and pulse oximetry accuracy in the context of COVID-19 infection, comprised 4330 white participants, 200 black participant, and 260 asian participants. Ethnicity did not appear to be a confounding factor in the outcome but, again, there was no specification of the degree of skin pigmentation in any of the ethnic subgroups, let alone a distinction between dark skinned asians versus light skinned white subjects [ 6 ].…”
mentioning
confidence: 99%
“…The sum total of these studies [ [1] , [2] , [3] , 5 , 6 ] represents a missed opportunity to clarify, more accurately, the significance of skin pigmentation in the management of subjects in whom pulse oximetry plays an important clinical role. Future studies should be based on the recognition that categorization by ethnicity(such as white versus black, versus asian) is no substitute for categorization by degree of skin pigmentation, given the recognition that the intensity of skin pigmentation varies enormously both in “black” subjects and in, for example, “asian” subjects from the Indian subcontinent.…”
mentioning
confidence: 99%